SPECIFICATION ANALYSIS OF FISHING POINTS ON PURCHASE DECISIONS IN SUKABUM: Manajemen pemasaran - ENDANG SE (Ekonomedia, 2021)
The purpose of this study was to determine the effect of Rod Material (X1), Rod Type (X2), Rod Section (X3), Rod Action (X4), Rod Power (X5), Ring Gudide (X6) and Lbs (X7) on decisions (Y ) The object of this research is Sukabumi. This research is descriptive associative using research instruments using primary data through questionnaires. The population is the anglers in Sukabumi with a sampling technique using purvosive sampling of 100 respondents. The results showed Rod Material (X1), Rod Type (X2), Rod Section (X3), Rod Action (X4), Rod Power (X5), Ring Gudide (X6) and Lbs (X7) on the decision (Y). For correlation analysis, it has a very strong influence. Meanwhile, in the t-test and F-test analysis, each independent variable either partially or simultaneously has a positive or direct influence on purchasing decisions which has a significance value of 0.05. In the analysis of the determination of the independent variable, it has an influence of 0.601 or 60.1% on purchasing decisions while the remaining 39.9% is influenced by variables not examined in this study.